POPULATION OF Ascaridia galli ACCORDING TO ITS PREDILECTION AFTER BEING TREATED WITH ARECA NUT INFUSION AND ITS ECONOMIC ANALYSIS - Bambang Sudarmanto; muzizat akbarrizki; wida wahidah mubarokah (Universitas Syiah Kuala, 2022)
This study aims to determine the effectiveness of Areca catechu Crude Aqueous Extract (ACCAE) as an anthelmintic, the number ofAscaridia galli worms in the duodenum, jejunum, and ileum after treatment, and an economic analysis. In this study, 50 female chickens wereused. The chickens were divided into 5 groups: Treatment 1, negative control (P1), which was given aquadestylates; treatment 2 (P2), which wasgiven infusion of ACCAE at a dose of 26 mg/mL; treatment 3 (P3), which was given infusion of ACCAE at a dose of 53 mg/mL; treatment 4(P4), which was given ACCAE with a dose of 79 mg/mL; and treatment 5 (P5) (positive control with pyrantel pamoat). Each group consisted of10 chickens. An examination was carried out that included weighing the population of adult worms according to their predilection 14 days aftertreatment. Weighing was carried out at the beginning before treatment, on the 7th day after treatment and on the 14th day after treatment. Thechickens were then euthenized, the intestinal worms were counted, and the economic analysis was calculated. Based on the results of the study, itcan be concluded that the best dose for removing A. galli worms is 79 mg/mL, and the location of the predilection of the intestine where the mostworms are found is the jejunum and the least is in the ileum. Economically, the highest income was obtained from treatment 4, namely the groupwith infusion of areca nut at a dose of 79 mg/mL.